Correlation between Aminotransferase Ratio (AST/ALT) and Other Biochemical Parameters in Chronic Liver Disease of Viral Origin (Delta Medical College Journal, 2015)
Background: In recent years the ratio of aspartate aminotransferase (AST) to alanine aminotransferase (ALT) in patients of chronic liver disease (CLD) of various origins has gained much attention. This variable is readily available, easy to interpret, and inexpensive and the clinical utility of the AST/ALT ratio in the diagnostic workup of patients with CLD is quite promising. Objective: The present study was designed to find out the link between aminotransferase (AST/ALT) ratio with commonly measured biochemical parameters of liver function tests in CLD of viral origin. Materials and method: This cross sectional study was carried out in the department of Biochemistry, Sir Salimullah Medical College, Dhaka, Bangladesh. Forty four biopsy proven diagnosed subjects of chronic viral hepatitis without cirrhosis of both sex were selected purposively. With aseptic precaution 5 mL venous blood was collected from each subject and common liver function tests (serum AST, ALT, AST/ALT ratio, alkaline phosphatase, total bilirubin, serum total protein, serum albumin, serum globulin, serum albumin/globulin ratio, prothrombin time) and viral serology (HBsAg, Anti HDV antibody, Anti HCV antibody) were performed. Data were analyzed by SPSS version 19 for Windows. Pearsons correlation test was done to determine association between AST/ALT with other biochemical parameters. Results: Mean(±SD) age of the study subjects was 32.55±10.55 years (range 20-50 years) with 48 (77.7%) male and 14 (22.6%) female subjects. Pearsons correlation test was done between AST to ALT ratio with other biochemical parameters and prothrombin time showed significant positive correlation (p